Contemporary Israel : domestic politics, foreign policy, and security challenges - Freedman, Robert Owen. (Boulder, CO : Westview Press, 2009)
"This essential survey brings together Israeli and American scholars to provide a much-needed balanced introduction to Israel's domestic politics and foreign policy." "Experts tackle this difficult subject in three parts: domestic politics, foreign policy challenges, and strategic challenges. Domestic topics include the Israeli Right and Left; religious, Russian, and Arab parties; the Supreme Court; and the economy Part two discusses Israel's complicated and often fractious relationships with the Palestinians and the Arab world, as well as its improved relations with Turkey and India and continuing close relationship with the United States. The Israel-Hizbollah War of 2006 and existential threats to Israel, including the threat from Iran, are detailed in part three. This compelling and authoritative coverage provides students with the necessary framework to understand Israel's political past and present, as well as the direction Israel is likely to take in the future."--BOOK JACKET.
Introduction / Robert O. Freedman -- Israel's domestic politics -- The Israeli right / Ilan Peleg -- After Rabin : the malaise of the Israeli Zionist left / Mark Rosenblum -- Israel's religious parties / Shmuel Sander and Aaron Kampinsky -- Israel's "Russian" parties / Vladimir (Ze'ev) Khanin -- Israel's Arab parties / Hillel Frisch -- Israel's supreme court / Pnina Lahav -- The Israeli economy / Ofira Seliktar -- Israel's foreign policy -- Israel and the Palestinians / Barry Rubin -- Israel and the Arab world / David W. Lesch -- Israel's strategic relations with Turkey and India / Efraim Inbar -- Israel and the United States / Robert O. Freedman -- Israel's security challenges -- Existential threats to Israel / Steven R. David -- Israel's 2006 war with Hizbollah : the failure of deterrence / Elli Lieberman.
Includes bibliographical references (p. 357-365) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
PROMPTCAT
Keywords: Arab-Israeli conflict -- Influence; Israel -- History -- 21st century; Israel -- Politics and government -- 21st century; Israel -- Foreign relations; Electronic books